Platelets interact with CD169+ macrophages and cDC1 and enhance liposome-induced CD8+ T cell responses - Grabowska, Joanna; Léopold, Valentine; Olesek, Katarzyna; Nijen Twilhaar, Maarten K.; Affandi, Alsya J.; Brouwer, Mieke C.; Jongerius, Ilse; Verschoor, Admar; van Kooten, Cees; van Kooyk, Yvette; Storm, Gert; van ‘t Veer, Cornelis; et al. (Frontiers in Immunology, 2023)
Historically platelets are mostly known for their crucial contribution to hemostasis, but there is growing understanding of their role in inflammation and immunity. The immunomodulatory role of platelets entails interaction with pathogens, but also with immune cells including macrophages and dendritic cells (DCs), to activate adaptive immune responses. In our previous work, we have demonstrated that splenic CD169+ macrophages scavenge liposomes and collaborate with conventional type 1 DCs (cDC1) to induce expansion of CD8+ T cells. Here, we show that platelets associate with liposomes and bind to DNGR-1/Clec9a and CD169/Siglec-1 receptors in vitro. In addition, platelets interacted with splenic CD169+ macrophages and cDC1 and further increased liposome internalization by cDC1. Most importantly, platelet depletion prior to liposomal immunization resulted in significantly diminished antigen-specific CD8+ T cell responses, but not germinal center B cell responses. Previously, complement C3 was shown to be essential for platelet-mediated CD8+ T cell activation during bacterial infection. However, after liposomal vaccination CD8+ T cell priming was not dependent on complement C3. While DCs from platelet-deficient mice exhibited unaltered maturation status, they did express lower levels of CCR7. In addition, in the absence of platelets, CCL5 plasma levels were significantly reduced. Overall, our findings demonstrate that platelets engage in a cross-talk with CD169+ macrophages and cDC1 and emphasize the importance of platelets in induction of CD8+ T cell responses in the context of liposomal vaccination.